Where Should I Publish My Sports Paper?. Issue 2 (2nd April 2020) - Swartz, Tim B.
ABSTRACT: With the increasing fascination of sport in society and the increasing availability of sport-related data, there are great opportunities to carry out sports analytics research. In this article, we discuss some of the issues that are relevant to publishing in the field of sports analytics. Potential publication outlets are identified, some summary statistics are given, and some experiences and opinions are provided.